Transformation of SiOx films into nanocomposite SiO₂(Si) films under thermal and laser annealing - Steblova, O.V.; Evtukh, A.A.; Bratus’, O.I.; Fedorenko, L.L.; Voitovych, M.V.; Lytvyn, O.S.; Gavrylyuk, O.O.; Semchuk, O.Yu. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Oxide-assisted growth of Si nanocrystals includes deposition of a siliconenriched
SiOx film at the first stage and annealing at the second one. The ion-plasma
sputtering method has been used for deposition of the SiOx film. The influence of
thermal and laser annealing on SiOx film properties has been investigated. Formation of
silicon nanoislands on oxide film surface has been observed by AFM both after thermal
and laser annealing. The height and surface density of the nanoislands depends both on
the silicon content in the initial SiOx film and temperature of thermal annealing. The
higher annealing temperature causes formation of large nanoislands, but their surface
density decreases. Comparison of nanoislands created at thermal and laser annealing
shows that in case of laser annealing the nanoislands are higher and their surface density
is lower. The intensity of laser irradiation influences on nanoisland parameters
significantly. The growth of electrical conductivity with thermal annealing temperature
has been observed. The influence of gas atmosphere during annealing is also significant
in case of higher temperatures. In case of laser annealing at the beginning at low laser
irradiation intensities, the SiOx film conductivity increases, but the following growth of
intensity causes the decrease in electrical conductivity.